Viral Hijacking of Mitochondrial Lysyl-tRNA Synthetase - Kaminska, Monika (American Society for Microbiology, 2007)
The primer for reverse transcription of the human immunodeficiency virus type 1 (HIV-1) genome is tRNA3Lys. During assembly of HIV-1 particles, tRNA3Lys is taken up from the host cell along with lysyl-tRNA synthetase (LysRS), the tRNA binding protein that specifically aminoacylates the different tRNA(Lys) isoacceptors. In humans, the cytoplasmic and mitochondrial species of LysRS are encoded by a single gene by means of alternative splicing. Here, we show that polyclonal antibodies directed to the full-length cytoplasmic enzyme equally recognized the two enzyme species. We raised antibodies against synthetic peptides that allowed discrimination between the two enzymes and found that mitochondrial LysRS is the only cellular source of LysRS detected in the virions. These results open new routes for understanding the molecular mechanisms involved in the specific packaging of tRNA3Lys into viral particles.